Expertise Development of Hospitality Students: Do Personality, Emotional Intelligence, and Learning Style Matter?. Issue 3 (2nd July 2016) - Wilson-Wünsch, Beverley; Beausaert, Simon; Tempelaar, Dirk; Gijselaers, Wim
ABSTRACT: Personality, emotional intelligence, and learning style are generally considered important success factors and career determinants in hospitality management. This study assesses the influence of these antecedents on the development of expertise in hospitality management. Correlational, ANOVA and hierarchical regression analyses demonstrated that (a) There is limited growth on cognitive performance measures while students are in school, however performance increases after a period in the workplace; (b) Personality, learning style and emotional intelligence showed zero to low correlations with cognitive performance; and (c) Extroversion, conscientiousness, emotional management and theorist learning style showed moderate positive correlations with several performance measures. The findings are partially in alignment with previous studies showing that personality, emotional intelligence and learning style play a role in expertise development in hospitality. It might be concluded that personality, emotional intelligence and learning style do seem important, they are not as important as has been argued in previous research.